Subtract. Express your answer as a polynomial in standard form.

6(3y^2-9y+8)-2(3-6y^2)

1 answer

6(3y^2-9y+8)-2(3-6y^2) = 6(3y^2-9y+8)-2(3)-2(-6y^2) = 18y^2-54y+20
Similar Questions
    1. answers icon 1 answer
  1. Given: f(x)=2x^2+x-3 and g(x)=x-1Express: f(x)⋅g(x)-[f(x)+g(x)] as a polynomial in standard form
    1. answers icon 1 answer
  2. PLS HELP ME!!I really need the answers to these few questions I need toturn them in ASAP. Simplify each polynomial. Write each
    1. answers icon 2 answers
    1. answers icon 7 answers
more similar questions